THE LEGAL PROTECTION OF HOSPITALS IN THE CASE OF NON-BPJS PATIENTS WHO ABSCOND AS A FORM OF BAD FAITH DUE TO THEIR INABILITY TO PAY - Wiweka, Wiweka (International Journal of Social Service and Research, 2024)
Hospitals often encounter financial difficulties when non-BPJS patients evade payment due to financial incapacity, with some institutions unfairly shifting the financial burden onto doctors. This situation raises serious legal, ethical, and employment concerns, especially in light of Law No. 17 of 2023 on Health, which mandates institutional responsibility for patient management. Meanwhile, Artificial Intelligence (AI) offers promising solutions for predicting and mitigating financial risks by identifying high-risk patients, though it introduces new challenges regarding data privacy, accountability, and liability. This study aims to explore the legal protections available to doctors when patients abscond without paying, and to propose a legal framework for integrating AI in healthcare to prevent such incidents. Using a normative legal approach, the research analyzes key provisions of Law No. 17/2023, employment regulations, and relevant case studies involving financial disputes between doctors and hospitals. The results show that imposing financial liability on doctors not only breaches employment principles but also contradicts healthcare regulations. Furthermore, AI can improve financial risk management by helping hospitals predict and prevent non-payment cases, though its implementation requires clear legal guidelines to avoid unintended consequences for medical staff. In conclusion, hospitals must bear financial responsibility for unpaid patient bills to protect doctors' legal rights. Additionally, a comprehensive regulatory framework for AI is essential to ensure that the technology is implemented fairly, safeguarding both healthcare professionals and patient interests.